How to Win the Haircare Competition in Bekasi Area - Annisa D Ambarwati; Joseph MJ Renwarin; M Richo Rianto; Matdio Siahaan; Djuni Thamrin; Dwi Entia; Silvia A Chairunnisah; Husni F Ramadhan; Hendy Tannady (Universitas 45 Surabaya, 2024)
Bekasi city is a promising market and is a satellite city with the largest population in Indonesia. One of the famous hair care brands in Indonesia is Ellips. Ellips is ranked first in the top of brands as proven in the last 5 consecutive years of top of mind. Ellipse products themselves are easy to find in supermarkets or shops throughout Indonesia. Apart from that, this product can also be found online, one of which is through the Shopee application. The purpose of this research is to determine the influence of price perceptions and sales promotions on purchasing decisions to purchase Ellips 5 in 1 hair vitamin products through the Shopee application. The method used in this research is a quantitative method with an online questionnaire survey via Google Form. The number of respondents was 150 people and the data processing tool used SmartPLS 4 software. The results of the study showed that price perception had a significant influence on purchasing decisions for Ellips 5 in 1 hair vitamin products through the Shopee application and sales promotions had a significant influence on purchasing decisions for Ellips 5 in 1 products. hair vitamins via the Shopee application. Thus, this research raises an interesting topic that explains the factors that influence purchasing decisions with a significant impact.